China's arable land wasting problem. Issue 3 (8th June 2021) - Chen, Wensheng
Abstract : Purpose: China's population–land contradiction is a crucial issue, and by deeply analyzing causes of wasting arable land, this article recommends some policies to avoid waste. Design/methodology/approach: Based on the current high-, middle- and low-class differentiation in the agricultural products' consumption structure against urban residents' rapid income growth, this article proposes that agricultural products with distinctive regional characteristics should be developed according to regional natural agricultural resources and market demand, so as to ensure that China's scarce arable land can be used effectively. Findings: Choices in regional agricultural production relate to operational farmers' enthusiasm for profitability and production, residential farmers' ability to ensure their own food security, agriculture's sustainable development and arable land resources' optimal allocation. Therefore, the varietal structure of agricultural products and regional production layout should be compatibly decided according to consumer demand and resource endowment. Originality/value: During the process of industrialization and urbanization, wasting of arable land has become a social development problem. On the basis of agriculture's regional resource endowment, this article reconstructs the functional positioning of various Chinese agricultural regions and solves the difficult problem of consumption structure transformation and homogeneous competition through the geographical division of labor, thereby optimizing allocation of arable land resources.